2006
DOI: 10.1371/journal.pmed.0030020
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Variation in the DC-SIGN–Encoding Gene CD209 Is Associated with Tuberculosis

Abstract: BackgroundTuberculosis, which is caused by Mycobacterium tuberculosis, remains one of the leading causes of mortality worldwide. The C-type lectin DC-SIGN is known to be the major M. tuberculosis receptor on human dendritic cells. We reasoned that if DC-SIGN interacts with M. tuberculosis, as well as with other pathogens, variation in this gene might have a broad range of influence in the pathogenesis of a number of infectious diseases, including tuberculosis.Methods and FindingsWe tested whether polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
5
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 41 publications
10
143
5
2
Order By: Relevance
“…25 Since the À871 SNP is absent in sub-Saharan Africans, our negative finding can only exclude a causal effect of À336, but we cannot confute a role for the À871/À336 haplotype in non-Africans. The apparent conflict of our data with that of Barreiro et al 5 can be explained by genetic heterogeneity (with different populations having differences in gene variants affecting risk) and is in agreement with the finding that their effect was mainly confined to people of Eurasian descent. One intronic SNPs found to be monomorphic in the Guinea-Bissau population sample.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…25 Since the À871 SNP is absent in sub-Saharan Africans, our negative finding can only exclude a causal effect of À336, but we cannot confute a role for the À871/À336 haplotype in non-Africans. The apparent conflict of our data with that of Barreiro et al 5 can be explained by genetic heterogeneity (with different populations having differences in gene variants affecting risk) and is in agreement with the finding that their effect was mainly confined to people of Eurasian descent. One intronic SNPs found to be monomorphic in the Guinea-Bissau population sample.…”
Section: Discussionsupporting
confidence: 82%
“…The first candidate was the C-type lectin DC-SIGN. A recent study by Barreiro et al 5 indicated an association between two DC-SIGN promoter SNPs (À871G and À336A) and a decrease in the risk of pulmonary TB. These authors investigated a South African population and concluded that the À871G/ À336A combination was largely confined to European and Asian populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammation is finely regulated through a complex network of transcription factors and post-translational mechanisms. [40][41][42] It is therefore conceivable that pathogen susceptibility or resistance might also in part reflect differences in gene expression. A future challenge for genetic association studies of human diseases will be to identify polymorphisms in non-coding sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the discussion of variants in TLR pathway genes described above may impact DC function. More recently, genetic studies of human DC-SIGN in South Africa have identified two promoter variants, -871G and -336A, that are associated with TB susceptibility [37]. The -336 SNP has also been found to be associated with Dengue fever and alters transcriptional activity at a Sp1-binding site, where the SNP resides [38].…”
Section: Disease Mechanism 2-dendritic Cells Genetics and Mtb Infectimentioning
confidence: 99%